Maslahah-driven Business Model Canvas: Advancing Home-based MSME Development in Medan - Sari, Della Puspita; Yanti, Nursantri; Nasution, Muhammad Lathief Ilhamy (IAIN Manado, 2026)
Home-based culinary MSMEs have seen substantial growth in response to economic instability and limited formal employment options. UMKM Mama Zahra, a local culinary business in Medan Tembung, has strong product acceptance but struggles with professional management and digital marketing. This study examines how the integration of the Business Model Canvas (BMC) and Maslahah principles from Islamic economics influences sustainable growth and managerial decision-making. Using a qualitative case study approach, data was gathered through in-depth interviews with the business owner and customers, participatory observation of operations, and document analysis. The data were analyzed using thematic analysis to identify patterns in BMC components and Maslahah dimensions (dharuriyyat, hajiyyat, and tahsiniyyah). The results show that Maslahah principles influence decisions in value proposition, customer relationships, and revenue streams by emphasizing ethical practices such as product quality, fair pricing, and customer trust. However, challenges in digital literacy and limited online marketing adoption hinder market expansion, weakening promotional strategies and scalability. For instance, the lack of social media presence and digital sales channels restricts customer acquisition beyond the local area, despite high customer loyalty. The study concludes that combining BMC and Maslahah principles fosters sustainable growth, focusing on economic viability, ethical practices, and community welfare. To enhance competitiveness and long-term success, targeted digital marketing training and continuous business mentoring are recommended for home-based culinary MSMEs.